Poland Syndrome. Case Presentation and Bibliographic Review - Lidia Torres Aja; Neylín Caballero Aja (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
Diverse changes in the morphology and structure of the mammary gland have been described as a result of the variation of the regulatory mechanisms of its development. Amastia is one of the less frequent congenital anomalies of the breast and it consists on the total absence of one or both glands. When it is unilateral it is generally also accompanied by the lack of the major and minor pectoral muscle besides other malformations, constituting what is known as Poland Syndrome. A case of a fifteen year old female patient is presented who shows the congenital absence of the right breast. This is the first case of Poland Syndrome diagnosed in Cienfuegos, this is why the publication of this case is considered of interest for the scientific community.